Species description, morphometric measurement and molecular identification of stingless bees (hymenoptera: apidae: meliponini) in meliponiculture industry in West Java Province, Indonesia - Purwanto, Hari; Trianto, Manap (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
This study was aimed to identify stingless bees commonly used in meliponiculture in Ciamis Regency, West Java Province, Indonesia based on morphological, morphometric, and molecular characters. Six species from three genera, namely Tetragonula, Heterotrigona, and Lepidotrigona, were obtained. There were Tetragonula laeviceps with morphological characteristics of a shiny black body and a body length of 3.42±0.02 mm (mean±SD); T. sarawakensis with morphological characteristics of a predominantly black body and a body length of 4.63±0.01 mm (mean±SD); T. cf. biroi with morphological characteristics of a body dominated by black and a body length of 3.94±0.02 mm (mean±SD); T. drescheri with morphological characteristics of a body dominated by a brownish-black color and body length of 4.64±0.01 mm (mean±SD); Heterotrigona itama with morphological characteristics of a dark black dominant body color and a body length of 4.84±0.02 mm (mean±SD); and Lepidotrigona terminata with morphological characteristics of a black dominant body color and body length of 4.63±0.01 mm (mean±SD). The sequences of stingless bees from Ciamis Regency, West Java Province have similarities (89-97%) with those of similar species of stingless bee in the GenBank database. The results of this study provide preliminary data contributing to the conservation and management as one the Indonesia's important biodiversity resources.